2022
DOI: 10.26599/bsa.2022.9050012
|View full text |Cite
|
Sign up to set email alerts
|

Hunt for mammalian sleep-regulating genes

Abstract: Genetics is one of the various approaches adopted to understand and control mammalian sleep. Reverse genetics, which is usually applied to analyze sleep in gene-deficient mice, has been the mainstream field of genetic studies on sleep for the past three decades and has revealed that various molecules, including orexin, are involved in sleep regulation. Recently, forward genetic studies in humans and mice have identified gene mutations responsible for heritable sleep abnormalities, such as SIK3, NALCN, DEC2, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Studies have found that the transcriptional repressor DEC2 is related to total sleep time in mammals (He et al, 2009 ). The polymorphism in the circadian clock gene PERIOD3 (PER3) could influence the sleep homeostasis of the individual (Viola et al, 2007 ), which may provide some explanations for this inter-individual difference (Funato and Yanagisawa, 2022 ). Zhang et al ( 2022a ) provided an umbrella review of PSG parameters in 27 neuropsychiatric diseases, suggesting that each disease may relate to a specific sleep profile.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the transcriptional repressor DEC2 is related to total sleep time in mammals (He et al, 2009 ). The polymorphism in the circadian clock gene PERIOD3 (PER3) could influence the sleep homeostasis of the individual (Viola et al, 2007 ), which may provide some explanations for this inter-individual difference (Funato and Yanagisawa, 2022 ). Zhang et al ( 2022a ) provided an umbrella review of PSG parameters in 27 neuropsychiatric diseases, suggesting that each disease may relate to a specific sleep profile.…”
Section: Discussionmentioning
confidence: 99%
“…The core molecular pathways and biochemical mechanisms that govern mammalian sleep regulation remain to be elucidated. Funato and Yanagisawa wrote a nice review of forward and reverse mouse genetics studies in search for mammalian sleep regulatory genes [8]. Notably, their previous studies of orexin knockout mice uncover the mechanistic link between orexin deficiency and human sleep disorder–narcolepsy [9].…”
mentioning
confidence: 99%